Recent Advances in Emulsions and Applications - Burgos-Díaz, César; Opazo-Navarrete, Mauricio; Morales, Eduardo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent years, there have been significant advances made in emulsion science in order to improve the quality and performance of different emulsion-based products using new techniques and structural designs. Emulsion systems have been employed for many years to develop a wide variety of commercial emulsified products, including food, pharmaceutical, and cosmetic products. Furthermore, this type of colloidal system has been utilized as a vehicle for the encapsulation and delivery of different bioactive compounds, such as antioxidants, vitamins, and fragrances. Therefore, a new generation of advanced emulsions may lead to products with enhanced quality and functionality.